101 innovation: a journey through UiTM's technological marvels / Ahmad Sabirin - Zoolfakar, Ahmad Sabirin; Tajul Ariffin, Julina; Mohd Yasim, Aisyah; Zainol, Nur Zafirah (UiTM Press, 2025)
This book is designed to serve as a valuable resource for UiTM staff, local and international industries, and individuals seeking cutting-edge innovations. Whether you are looking to collaborate with UiTM researchers, explore new technologies, or discover solutions to industry needs, you will find a wealth of opportunities within these pages. Each product featured in this book represents the culmination of rigorous research, creative ingenuity, and a commitment to excellence.